Implementation of Line 1 Imported Container Fumigation : Logistics Cost Efficiency and National Anti-Corruption Program Support - Dhea Putriana Cahya Azizah; Otri Wani Sihaloho; Dyah Ratnaningsih; Bugi Nugraha (Pusat Riset dan Inovasi Nasional, 2025)
Import-export activities cannot be separated from the term logistics costs, currently the amount of logistics costs in Indonesia has reached 17%. One of the reasons for the high logistics costs is the level of efficiency and effectiveness of the logistics chain, such as the unavailability of fumigation services in the line 1 port area. With the hope of reducing logistics costs, PT one single billing system, This is in accordance with the focus of 1 STRANAS PK which encourages system integration in port services. The implementation of STRANAS PK within the port area is intended to reduce corruption cases triggered by incompatibility between service systems. This research is intended to determine whether the implementation of imported container fumigation services in the line 1 area as a follow-up to STRANAS PK has been implemented and has an effective influence on logistics costs. The method in this research uses a quantitative type, with simple calculations which are reinforced with t-tests by the SPSS version 26 application. This research proves that there are savings that occur in logistics costs amounting to IDR 551,562,000, for 660 40ft imported containers that are fumigated with Methyl Bromide 16 mg dose if the fumigation process of imported containers is carried out in the line 1 area, and in the t-test via SPSS a significant value of 0.000 < 0.05 is obtained, meaning that all variables significantly influence the efficiency variable. So it can be concluded that the line 1 cost variables (X1) and line 2 costs (X2) have an influence on the efficiency variable (Y). Fumigation services in the line 1 area are in accordance with STRANAS PK's focus on port governance, and of course have a big impact on effectiveness and efficiency in logistics costs.